1989
DOI: 10.1159/000115917
|View full text |Cite
|
Sign up to set email alerts
|

Premotor Programming and Cortical Processing in the Cerebral Cortex

Abstract: Slow brain potentials were averaged from 12–15 EEG records (t = DC or 5 s) before and during voluntary hand movement and writing, spatial vision, language, and calculation tasks without vocalization and with visual fixation. EOG and writing pressure or EMG were recorded simultaneously. Skilled actions caused largest negative potentials in the contralateral sensorimotor hand area. Left-sided lateralization or bilaterally equal surface-negative potential shifts appeared during language and calculation tasks in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In particular, converging evidence has been accumulated that the left parietooccipito-temporal region of the brain is crucial in calculation processes. One line of evidence comes from electrophysiological studies (Altenmüller, Jung, Winkler, & Landwehrmeyer, 1989;Inouye, Shinosaki, Iyama, & Mastumoto, 1993;Papanicolaou, Schmidt, Moore, & Eisenberg, 1983;Shepard & Gale, 1982). Altenmüller et al (1989) found a preponderance of left posterior activation in 65% of his subjects as indexed by a slow negative DC-shift during a complex addition task (i.e.…”
mentioning
confidence: 99%
“…In particular, converging evidence has been accumulated that the left parietooccipito-temporal region of the brain is crucial in calculation processes. One line of evidence comes from electrophysiological studies (Altenmüller, Jung, Winkler, & Landwehrmeyer, 1989;Inouye, Shinosaki, Iyama, & Mastumoto, 1993;Papanicolaou, Schmidt, Moore, & Eisenberg, 1983;Shepard & Gale, 1982). Altenmüller et al (1989) found a preponderance of left posterior activation in 65% of his subjects as indexed by a slow negative DC-shift during a complex addition task (i.e.…”
mentioning
confidence: 99%